Formation of DNA adducts in wild-type and transgenic mice expressing human sulfotransferases 1A1 and 1A2 after oral exposure to furfuryl alcohol - Høie, Anja Hortemo (Mutagenesis, 2015)
Furfuryl alcohol (FFA) is present in many heat-treated foods as a result of its formation via dehydration of pentoses. It is also used legally as a flavouring agent. In an inhalation study conducted in the National Toxicology Program, FFA showed some evidence of carcinogenic activity in rats and mice. FFA was generally negative in conventional genotoxicity assays, which suggests that it may be a non-genotoxic carcinogen. However, it was recently found that FFA is mutagenic in Salmonella strains expressing appropriate sulfotransferases (SULTs), such as human or mouse SULT1A1. The same DNA adducts that were formed by FFA in these strains, mainly N (2)-((furan-2-yl)methyl)-2′-deoxyguanosine (N (2)-MF-dG), were also detected in tissues of FFA-exposed mice and even in human lung specimens. In the present study, a single oral dose of FFA (250mg/kg body weight) or saline was administered to FVB/N mice and transgenic mice expressing human SULT1A1/1A2 on the FVB/N background. The transgenic mice were used, since human and mouse SULT1A1 substantially differ in substrate specificity and tissue distribution. DNA adducts were studied in liver, kidney, proximal and distal small intestine as well as colon, using isotope-dilution ultra performance liquid chromatography (UPLC–MS/MS). Surprisingly, low levels of adducts that may represent N (2)-MF-dG were detected even in tissues of untreated mice. FFA exposure enhanced the adduct levels in colon and liver, but not in the remaining investigated tissues of wild-type (wt) mice. The situation was similar in transgenic mice, except that N (2)-MF-dG levels were also strongly enhanced in the proximal small intestine. These different results between wt and transgenic mice may be attributed to the fact that human SULT1A1, but not the orthologous mouse enzyme, is strongly expressed in the small intestine.